2009
DOI: 10.1111/j.1939-1676.2008.0236.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Novel Liquid Formulation of L‐Thyroxine for Once Daily Treatment of Dogs with Hypothyroidism

Abstract: Background: A liquid solution of levothyroxine (L-T4) is available for treatment of canine hypothyroidism. Hypothesis: Once daily oral administration of a liquid L-T4 solution is effective and safe for controlling hypothyroidism in dogs.Animals: Thirty-five dogs with naturally occurring hypothyroidism. Methods: Dogs received L-T4 solution PO once daily at a starting dosage of 20 mg/kg body weight (BW). The dose was adjusted every 4 weeks, based on clinical signs and peak serum total T4 (tT4) concentrations. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…The pharmacokinetic profiles of tT 4 in hypothyroid dogs in this study provide pharmacological evidence, in addition to clinical data published earlier, 3 that once daily dosing of L-T 4 solution is an appropriate treatment for spontaneous primary hypothyroidism in dogs. This dosing schedule could improve treatment compliance and thus decrease apparent treatment failure.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The pharmacokinetic profiles of tT 4 in hypothyroid dogs in this study provide pharmacological evidence, in addition to clinical data published earlier, 3 that once daily dosing of L-T 4 solution is an appropriate treatment for spontaneous primary hypothyroidism in dogs. This dosing schedule could improve treatment compliance and thus decrease apparent treatment failure.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is in agreement with clinical observations that this L-T 4 solution at a dosage of 20 lg/kg once daily, was effective in most hypothyroid dogs. 3 In that study, clinical signs of hypothyroidism improved or resolved in 91% of the dogs after 4 weeks of treatment at this dosage and this dosage was suitable for once daily maintenance in 79%, with 30 lg/kg required for 15%, and 10-15 lg/kg for 6%. The peak tT 4 concentration (4-6 hours after dosing) of 51 nmol/L (median) reported in that clinical efficacy study was very close to our results (46 AE 14.1 nmol/L at 4 hours, 46 AE 12.5 nmol/L at 6 hours).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The plasma half-life of L-T 4 sodium in dogs ranges from 9 to 14 hours and depends, in part, on the dosage and frequency of administration, with higher dosages and more frequent administration associated with a shorter half-life of L-T 4 sodium (Nachreiner et al, 1993;Le Traon, 2007). Most studies have shown that the majority of dogs have a good clinical response to treatment with once daily L-T 4 sodium; however dose adjustments are required in 20% to 50% of dogs started on once a day therapy (Le Traon et al, 2009;Dixon et al, 2002). At this dosage, mean time to peak serum T 4 concentration was 3.8 ± 2.0 hours after L-T 4 sodium administration.…”
Section: Treatmentmentioning
confidence: 99%
“…The investigators chose to administer levothyroxine once daily based on the resolution of clinical abnormalities of hypothyroidism in dogs supplemented in a similar manner. 20,21 Although once daily dosing results in more fluctuation in serum T 4 concentrations compared to twice daily dosing, the duration of action of T 4 is longer than its plasma half-life. [22][23][24][25][26] In previous studies of the HPTA, dogs were administered levothyroxine twice daily, making comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%